Architecture totalitaire et commande autoritaire. La place des architectures monumentales des régimes totalitaires dans l’historiographie - Jean-Pierre Frey (Cybergeo, 2017)
The impressive image that totalitarian regimes imposed through monumental architecture without consulting the masses is too often confused with the massive state investment and authoritarian and dictatorial political regimes sponsors. The sometimes exorbitant orders and programs are however not necessarily incompatible neither with the architectural creativity nor with achievements that may flatter the nationalism of common sense or peoples ways to consolidate their identity building, which always plays the long term and on a patrimonialisation largely based on amnesia concrete production conditions of the premises. The architecture of the totalitarian regimes is particularly suited to reflection of broader scope than the periods and regimes considered the relationship between control, program, project and reception. The meaning of the monuments appear much richer than we imagine at first look. To judge by an aesthetic perception summarily if one takes the trouble to reconsider this type of production and consumption according to complexity of a real trial goes well beyond the simple alleged perpetrators or responsible for operations or construction period assimilated to the significance of a political regime.